Interface Analysis of the Pickup and Destination Location Search Feature in the GoRide Menu of the Gojek Application - Pratama, Riski Yuniar; Salsabila, Yumna Salma; Alifi, Revand Daffa Firza; Maulana, Ilham; Denyana, Naufal Tipasha; S, Febriany Valentin; Arini, Florentina Yuni (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 5 No 3 (2024): JITTER, Vol.5, No.3, December 2024, 2024)
The effective implementation of User Interface (UI) components is a crucial aspect in determining the success of mobile applications, including Gojek. This research aims to evaluate the implementation of UI components in the location search feature for pickup and destination within the GoRide menu of the Gojek application using the Heuristic Usability method. This method consists of ten heuristic principles proposed by Jakob Nielsen, which are used to identify usability issues that may potentially affect the user experience. The research was conducted using a qualitative approach, where a series of evaluations were carried out by UI experts on the user interface of the location search feature in GoRide. The results of the study indicate several areas for improvement related to design consistency, visibility of system status, clarity of error messages, and efficiency of use in the location search feature, which impact user efficiency and satisfaction. The implications of these findings can serve as guidelines for developers in enhancing the quality of the location search interface in GoRide to improve the overall user experience. This study also contributes to the development of UI analysis methodologies and heuristic-based usability evaluation of applications in Indonesia.